2006
DOI: 10.1111/j.1467-8624.2006.00860.x
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Control, Social Context, and Individual Differences in Behavioral and Cortisol Responses to Novelty in Infant Rhesus Monkeys

Abstract: The effects of appetitive controllability on behavioral and cortisol reactivity to novelty in 12 infant rhesus monkeys were studied. Surrogate-peer-reared infants had homecage access to food treats contingently via lever pressing ("master") or noncontingently ("yoked") for 12 weeks from postnatal month 2. Masters lever-pressed more, but did not differ in baseline cortisol. At month 5, infants were exposed to a novel environment in social groups and individually. Masters were significantly more active and exhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…In line with expectations, researchers found that higher versus lower predictability and controllability of stressful events mitigated or exacerbated, respectively, subsequent levels of negative emotions (Mineka, Cook, & Miller, 1984; Seligman, 1975). The effects of a sense of control on behavioral and physiological outcomes have also been examined in relation to appetitive-oriented situations within samples of rhesus monkeys; results indicated that monkeys raised with greater control over appetitive goals (i.e., food acquisition) responded more actively and with decreased cortisol reactivity when presented with novel situations compared with monkeys that were allowed less control over food access (Roma, Champoux, & Suomi, 2006). Relatedly, infant monkeys who were raised by mothers experiencing unpredictable foraging conditions exhibited greater levels of corticotropin-releasing hormone (CRH) than infant monkeys raised by mothers experiencing either a consistent overabundance or a consistent scarcity of food (Coplan et al, 1996).…”
Section: Triple Vulnerability Theorymentioning
confidence: 99%
“…In line with expectations, researchers found that higher versus lower predictability and controllability of stressful events mitigated or exacerbated, respectively, subsequent levels of negative emotions (Mineka, Cook, & Miller, 1984; Seligman, 1975). The effects of a sense of control on behavioral and physiological outcomes have also been examined in relation to appetitive-oriented situations within samples of rhesus monkeys; results indicated that monkeys raised with greater control over appetitive goals (i.e., food acquisition) responded more actively and with decreased cortisol reactivity when presented with novel situations compared with monkeys that were allowed less control over food access (Roma, Champoux, & Suomi, 2006). Relatedly, infant monkeys who were raised by mothers experiencing unpredictable foraging conditions exhibited greater levels of corticotropin-releasing hormone (CRH) than infant monkeys raised by mothers experiencing either a consistent overabundance or a consistent scarcity of food (Coplan et al, 1996).…”
Section: Triple Vulnerability Theorymentioning
confidence: 99%
“…Beyond toys, it has been suggested that providing animals with choice and control in their environment can result in further indications of improved welfare (e.g., [42][43][44]). Studies have shown, for example, that when animals can choose whether to be inside or outside [45,46], control the timing of when they receive food or treats [47][48][49][50], or control when music or a light is on or off [47,50,51], this can result in less agitation, a reduction in stereotypic behaviors, calmer activity patterns, lower cortisol levels, more exploratory behavior, and more social play. And when marine mammals are given increased choices within training sessions, such as ways to explicitly choose reward types, behaviors, partners, or even to end the session, this has led to increased interest and participation [52,53].…”
Section: Beyond Physical Welfarementioning
confidence: 99%
“…Various studies have used exposure to novel environments, novel social partners or novel inanimate objects to investigate individual variation in behavioral reactions (Kinnally, Whiteman, Mason, Mendoza, & Capitanio, ; Mason, Capitanio, Machado, Mendoza, & Amaral, ; Miller, Bard, Juno, & Nadler, ; Roma, Champoux, & Suomi, ). Furthermore, when multiple researchers use similar methods to elicit behavioral variation, it is possible to build up a wider picture of the relationships among genetics, behavior and downstream consequences.…”
Section: Genetic Effects On Response To Novel Objectsmentioning
confidence: 99%